Modulation of Horizontally Acquired Genes by the Hha-YdgT Proteins in Salmonella enterica Serovar Typhimurium - Vivero, Aitziber (American Society for Microbiology (ASM), 2008)
We describe a transcriptomic study of the effect of hha and ydgT mutations in Salmonella enterica serovar Typhimurium. A large number of genes showing altered expression are located in AT-rich horizontally acquired DNA sequences. Many of these genes have also been reported to be targets for H-NS. As Hha and YdgT interact with H-NS, our findings strongly suggest that Hha and/or YdgT must form complexes with H-NS when they silence these DNA regions.